Safety and effectiveness of a fixed-dose combination of olmesartan, amlodipine, and hydrochlorothiazide in clinical practice - Bramlage, Peter; Fronk, Eva Maria; Wolf, Wolf Peter; Smolnik, RüDiger; Sutton, Gemma; Schmieder, Roland (Vascular Health and Risk Management, 2015)
Clinical trials indicate that the use of fixed-dose combinations (FDCs) is associated with a higher level of treatment adherence and prolonged blood pressure (BP) control. The aim of this study was to document the safety and effectiveness of the FDC olmesartan/amlodipine/hydrochlorothiazide in patients with essential hypertension in clinical practice.This multicenter, prospective, 24-week, noninterventional study enrolled 5,831 patients from primary care offices in Germany and Austria. Inclusion criteria were a diagnosis of essential hypertension and newly initiated treatment with the FDC.The mean age of patients was 63.5 years, almost 50% of patients had a time since diagnosis of essential hypertension of over 5 years, and approximately 70% of patients had at least one cardiovascular risk factor, including 29.4% of patients with diabetes mellitus. Following approximately 24 weeks of treatment, the mean reduction in systolic/diastolic BP was 29.0/14.0 mmHg, a BP response was observed by 94.2% of patients, and a target BP of <140/90 mmHg was attained in 67.5% of patients. At least one adverse drug reaction (ADR) was experienced by 1.2% of patients, with the most common being peripheral edema. Subanalyses demonstrated that the following factors did not have a significant influence on the ADR rate: age (<65 years versus >=65 years), diabetes mellitus (no/yes), cardiovascular risk (low/high), and concomitant medication (no/yes).This study demonstrates that in clinical practice, treatment with the three-drug combination as an FDC tablet resulted in a very high proportion of patients with a BP response and control, accompanied by a very low rate of ADRs.
EVALuna2:3750